2005
DOI: 10.1007/s00262-005-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of an allogeneic whole-cell tumor vaccine expressing xenogeneic gp100 and its implementation in a phase II clinical trial in canine patients with malignant melanoma

Abstract: A xenogeneic melanoma-antigen-enhanced allogeneic tumor cell vaccine (ATCV) is an appealing strategy for anti-cancer immunotherapy due to its relative ease of production, and the theoretical possibility that presentation of a multiplex of antigens along with a xenogeneic antigen would result in cross-reaction between the xenogeneic homologs and self-molecules, breaking tolerance and ultimately resulting in a clinically relevant immune response. In this study, we evaluated the efficacy of such a strategy using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 28 publications
0
57
1
2
Order By: Relevance
“…Even though the PS-CT was less effective than the CS-CT to control the disease, it was significantly better than only surgery (PS-ST: Po0.01 Table 4 and CS-ST: Po0.05, Fisher's Exact test). Thus, this updated study suggests that this CT holds the most promise for cancer patients with minimal residual disease, [6][7][8]16,20 and corroborates the negative prognostic factor for the presence of local disease that substantially shortened patients median overall survival (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Even though the PS-CT was less effective than the CS-CT to control the disease, it was significantly better than only surgery (PS-ST: Po0.01 Table 4 and CS-ST: Po0.05, Fisher's Exact test). Thus, this updated study suggests that this CT holds the most promise for cancer patients with minimal residual disease, [6][7][8]16,20 and corroborates the negative prognostic factor for the presence of local disease that substantially shortened patients median overall survival (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3] We have widely discussed the potential of comparative cancer gene therapy as a preclinical phase for human clinical trials. 5 Different gene therapy approaches have been reported for canine spontaneous melanoma such as: (i) ex vivo human interleukin-2 (hIL-2) producing xenogeneic cells, 6 human granulocytemacrophage colony-stimulating factor (hGM-CSF) producing autologous tumor cells, 7 human gp100 producing allogeneic tumor cells; 8 and (ii) in vivo gene transfer of enterotoxin-B plus GM-CSF, 9 xenogeneic human 10 or murine 11 tyrosinase, human FasL, 12 IL-12 (ref. 13) and CD40 ligand.…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical trial using allogeneic whole cell vaccination, the canine melanoma cell line, 17CM98, was transfected with xenogeneic human gp100 (a melanocyte specific trans-membrane protein i.e.i.e. a melanoma TAA), killed by irradiation and administered intra-dermally to dogs in an attempt to break tolerance with a combination of self and xenogeneic antigens (Alexander et al, 2006). Hogge and colleagues adopted a Figure. 1 The melanogenesis pathway, enzymes involved in the pathway that act as differentiation antigens are indicated with italics.…”
Section: Whole Cell Vaccinationmentioning
confidence: 99%
“…10 Immunotherapy in combination with suicide gene therapy (SG) holds the most promise for malignant melanoma patients with minimal residual disease after surgery. [11][12][13] In a previous controlled study in more than 100 dogs, we demonstrated that repeated concurrent injections of the suicide gene system and engineered xenogeneic IL-2-and GM-CSF-secreting cells into the tumor bed, substantially controlled tumor growth and improved disease-free and overall survival in the treated animals compared to untreated or surgerytreated controls.…”
Section: Introductionmentioning
confidence: 99%